1970
DOI: 10.1039/tf9706602732
|View full text |Cite
|
Sign up to set email alerts
|

Electron-diffraction study of the molecular structure of tetramethyldiphosphine

Abstract: The molecular structure of tetramethyldiphosphine in the gas phase has been determined by electron diffraction. The study required a gas-nozzle temperature of 170°C, obtained by using hot compressed air. The molecule can be described by seven structural parameters from which all the 52 different interatomic distances can be calculated. All 52 distances were included in the fullmatrix least-squares refinements which were performed. The final values of the seven independent parameters are C-H = 1.109f0.009 A, C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1971
1971
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Infrared-Raman vibrational studies on P2(CH3)4 indicate that the structure for the solid phase is trans but that the liquid Hodges, Su, and Bartell is a trans-gauche mixture.43 A gas-phase electron diffraction study of the molecule was interpreted in terms of a "skewed" trans conformation.44 On the basis of vibrational studies, it was concluded that conformational differences also exist between the liquid,45,46 solid,47 and gas48 phases of IPzM4. For example, the P-P bond lengths in P2 (CH3) 44 Tables of other P--P bond lengths and conformations in various diphosphines and hydrazines are included in the supplementa1 y material and in a doctoral dissertation.14 Of the various diphosphines studied to date, F2PPH213 is perhaps the best candidate for K delocalization across the P-P bond. Some rules of thumb for predicting conformation stabilities are discussed by Durig,et ~1 .…”
Section: Results For P2(cf3)4mentioning
confidence: 99%
“…Infrared-Raman vibrational studies on P2(CH3)4 indicate that the structure for the solid phase is trans but that the liquid Hodges, Su, and Bartell is a trans-gauche mixture.43 A gas-phase electron diffraction study of the molecule was interpreted in terms of a "skewed" trans conformation.44 On the basis of vibrational studies, it was concluded that conformational differences also exist between the liquid,45,46 solid,47 and gas48 phases of IPzM4. For example, the P-P bond lengths in P2 (CH3) 44 Tables of other P--P bond lengths and conformations in various diphosphines and hydrazines are included in the supplementa1 y material and in a doctoral dissertation.14 Of the various diphosphines studied to date, F2PPH213 is perhaps the best candidate for K delocalization across the P-P bond. Some rules of thumb for predicting conformation stabilities are discussed by Durig,et ~1 .…”
Section: Results For P2(cf3)4mentioning
confidence: 99%
“…It is further interesting to note that the isoelectronic radicals PF2, SO 2 and C102, in which the central atoms (P, S and C1) are consecutive atoms in the periodic table, have in common that they do not unite to molecules with strong central bonds. Two PF 2 radicals form a (staggered) molecule P2F4 with P-P [2.281 (6) ,~; Hodges, Su & Bartell, 1975] ca 0.1 /~ longer than those in P2(CF3) 4 [2.182 (16) /~; Hodges et al, 1975] and P2(CH3)4 [2.192 (9) ,/k;McAdam, Beagley & Hewitt, 1970]. As we have seen above, in the (eclipsed) $20~-ion the bond between the two SO2 units is extraordinarily long (2.39 /i,).…”
Section: Discussion Of the Dithionite Ionmentioning
confidence: 99%
“…2 This may be a consequence of description of the gas-phase mixture of two conformers with considerably different P-P-C angles by a single-conformer model in the original electron diffraction study. 6 The theoretical calculations predict one of the angles to be up to 7Њ larger in the gauche conformer than the corresponding angle in the anti conformer. Unexpectedly, the performance of the B3LYP method worsened with the increase of the basis set, with the closest agreement with the experimental data achieved in the calculations applying the smallest 3-21G* basis set.…”
Section: Molecular Geometriesmentioning
confidence: 99%
“…5 A later gas-phase electron diffraction study at 170 ЊC found the experimental data to be consistent with a single distorted anti conformation of the molecule. 6 The observed 16Њ deviation from the anti form was attributed to the large-amplitude torsional motion about the central P-P bond. A study of the gas-phase IR spectrum resulted in the conclusion that the gauche conformer predominates over anti in the ratio 3 : 2.…”
Section: Introductionmentioning
confidence: 99%